2021
DOI: 10.1021/acs.energyfuels.1c02967
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Carbon Nanotube Dual-Decorated SiOx Composite Anode Material for Lithium-Ion Batteries

Abstract: In this study, a three-dimensional graphene- and carbon nanotube (CNT)-decorated SiO x composite material (SiO x -Gr-CNT) was synthesized. The dual carbon components were introduced by a simple one-step method of high-energy ball milling. The corresponding SiO x -Gr-CNT composite electrode exhibited superior lithium storage performance because the graphene and CNT components form a flexible network with high conductivity decorating on SiO x . The network is beneficial for the improvement of the conductivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Therefore, it is very important for the design of carbon that introducing as little carbon as possible to get the carbon layer that matches the material particle size and has uniform and orderly morphology. neighboring CNTs, which improved the maintenance of conductive paths and structural integrity of SiO x [102]. The stable cycling performance of the composites can be maintained with the retention of 88% of its initial charge capacity after 100 cycles (Fig.…”
Section: Coated Sio X /C Compositesmentioning
confidence: 92%
“…Therefore, it is very important for the design of carbon that introducing as little carbon as possible to get the carbon layer that matches the material particle size and has uniform and orderly morphology. neighboring CNTs, which improved the maintenance of conductive paths and structural integrity of SiO x [102]. The stable cycling performance of the composites can be maintained with the retention of 88% of its initial charge capacity after 100 cycles (Fig.…”
Section: Coated Sio X /C Compositesmentioning
confidence: 92%
“…On the surface of the composites, the binding energy of C atoms at 284.33, 284.82, 286.59, and 288.93 eV are attributed to the various chemical structures of the C atoms derived from CSi, CC, CO, and CO, respectively. The Si atom in the different chemical structure can be divided into (CH 3 ) 2 SiC, (CH 3 ) 2 SiO 2/2 , (CH 3 )SiO 3/2 , SiO 1.5 , SiO 2 , whose binding energies are at 101.51, 102.10, 102.90, 103.62, and 104.69 eV, respectively 34 . The changes of C and Si atoms in various structures on the surface of the composites before and after the ablation are summarized in Table 9 and Table 10.…”
Section: Resultsmentioning
confidence: 99%
“…On the surface of the composites, the binding energy of C atoms at 284. 33 34 The changes of C and Si atoms in various structures on the surface of the composites before and after the ablation are summarized in Table 9 and Table 10. By comparison, the Si atom in the structure of (CH 3 ) 2 SiC on the surface of T700CF/PPSOA-1 is higher than that on the surface of T700CF/PPSOA-2 since the block PSA in the PPSOA-1 copolymer is larger than that in the PPSOA-2 before the ablation.…”
mentioning
confidence: 99%
“…Previous research has indicated that the use of carbon-based materials is essential for improving the performance and stability of these anodes. 41 He et al 42 have provided a comprehensive review of the progress made with silicon− graphite materials and have proposed several promising directions for their industrialization. One strategy that shows great potential is the utilization of three-dimensional (3D) cross-linked binders.…”
Section: Sio X Heteroatom Addition Designmentioning
confidence: 99%
“…The successful implementation of silicon- and SiO x -based anodes remains a significant challenge for achieving industrial application cycles. Previous research has indicated that the use of carbon-based materials is essential for improving the performance and stability of these anodes . He et al .…”
Section: Sio X Heteroatom Addition Designmentioning
confidence: 99%